Increased taxonomic and functional similarity does not increase the trophic similarity of communities. Issue 1 (9th November 2015) - Pool, Thomas K.; Cucherousset, Julien; Boulêtreau, Stéphanie; Villéger, Sébastien; Strecker, Angela L.; Grenouillet, Gaël
Abstract: Aim: Despite a long‐standing research interest in the association between the biodiversity (i.e. taxonomic and functional composition) and trophic structure of communities, our understanding of the relationship remains limited. Community assembly theory predicts that niche partitioning will result in communities with a diverse array of functional traits, which in turn may facilitate a correspondingly diverse array of trophic interactions that define the trophic niche of those communities. The aim of our study is to test this prediction. Location: North America. Methods: We built a database composed of functional traits and stable isotope values (δ 13 C and δ 15 N) for 63 freshwater fish communities containing 109 species in 34 lentic and 29 lotic ecosystems. First, using linear mixed models (i.e. an alpha‐diversity approach), we tested whether the taxonomic diversity of communities was positively associated with their functional diversity and if their functional diversity was positively associated with their trophic diversity. Second, we assessed the taxonomic, functional and trophic similarity of communities using multiple regression on distance matrices (MRM) and their respective 'turnover' and 'nestedness‐resultant' components to test if the taxonomic similarity of communities was positively correlated with their functional similarity and if their functional similarity was positively associated with their trophic similarity (i.e. a beta‐diversity approach). Results: We found that the functional diversity of communities increased as their taxonomic diversity increased. Similarly, the trophic diversity of communities increased as their functional diversity increased. The pairwise taxonomic and functional similarity of communities were also positively associated, but there was a weak relationship between the functional and trophic similarities of communities. Main conclusions: Our study demonstrates that communities with similar functional characteristics can have disparate food web structures, suggesting that additional site‐specific factors influence community variation in trophic niche geometry. Determining the relative importance of functional characteristics and site‐specific factors in shaping trophic interactions is crucial for a better understanding of how future species loss and species introductions will affect food web structure and ecosystem functioning.